2016
DOI: 10.1166/jnn.2016.11387
|View full text |Cite
|
Sign up to set email alerts
|

Morphologically Controlled Synthesis of Hydroxyapatite and Its Bioactivity on Osteoblast Cells

Abstract: Surface morphology has great influence on bioactivity of materials. It is important to understand biological responses of materials via structured surface design, which is essential for development of bioactive bone repair materials. Herein, different morphologies of hydroxyapatite were obtained by soft templates in a hydrothermal process. The morphology of the hydroxyapatite was modified from nanorods to flake-like and dandelion-like shapes by using cetyltrimethyl ammonium bromide, ammonium tartrate and triso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The difference surface properties of the two kind hydroxyapatites may contribute to this result. Qian Huang et al also demonstrated that osteoblasts reacted sensitively towards the hydroxyapatite with different morphology and size [43] . In the present study, the nano-HAP was rodlike and micro-HAP was spherical, their bore diameters were different, the pore size between nano-HAP particles were about 3-4 nm as shown in BJH test in Figure 1.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…The difference surface properties of the two kind hydroxyapatites may contribute to this result. Qian Huang et al also demonstrated that osteoblasts reacted sensitively towards the hydroxyapatite with different morphology and size [43] . In the present study, the nano-HAP was rodlike and micro-HAP was spherical, their bore diameters were different, the pore size between nano-HAP particles were about 3-4 nm as shown in BJH test in Figure 1.…”
Section: Cell Viabilitymentioning
confidence: 99%
“…The morphology of HAp particles is another important factor that has great influence on their biological properties. For example, Huang et al [47] prepared different morphologies of HAp with nanorods, flake-like and dandelion-like shapes represented in Figure 2.13A by a hydrothermal process using cetyltrimethyl ammonium bromide (CTAB), ammonium tartrate (AT) and trisodium citrate (TSC) as soft templates, respectively. They suggested that the rough surface of material has more beneficial for cell adhesion and proliferation than others.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…The result indicated that rod-like HAp nanoparticles might be an optimal morphology for potential biomedical applications. [47] Besides particle size and morphology, previous studies have provided evidence that the surface charge of HAp particles also affects the bone cell behavior. From Chen et al research, [48] they proposed the influence of surface charges of HAp on the intracellular uptake, cell viability and proliferation of osteoblast cells (MC3T3-E1) by functionalization with similar carboxylic acid compounds to minimum interference from other factors: 12-aminododecanoic acid (amine group on side chain, positive charge), dodecanedioic acid (carboxyl group on side chain, negative charge) and dodecanoic acid (methyl group, neutral) as demonstrated in Figure 2.14A.…”
Section: Literature Reviewsmentioning
confidence: 99%
See 1 more Smart Citation